A generalised marine planning framework for site selection based on ecosystem services. (February 2021) - von Thenen, Miriam; Hansen, Henning Sten; Schiele, Kerstin S.
Abstract: A new proposed framework to assess sustainability impacts of maritime spatial plans (MSP-SA) utilises the ecosystem service (ES) concept to address the often-lacking social sustainability of the plans. This study departs in the MSP-SA framework and applies it to the (emerging) sea use of mussel farming. Informed by a literature review and two surveys, it is investigated whether the benefits and impacts of mussel farming can be related to underlying ES and relevant planning questions. The results show that most benefits and impacts of mussel farming can be connected to ES and reveal different user-environment-beneficiary interactions, ranging from conflicts to synergies. The marine planning framework is structured into different planning phases and it is shown that the ES concept can contribute to a normative vision, strategic objectives, and site-specific operational questions. Studying the different user-environment-beneficiary interactions can reveal who benefits and who loses from planning decisions. While the marine planning framework developed in this study is targeted at mussel farming, the approach can be adapted to other uses and planning areas and can contribute to social and equity aspects in MSP by considering the receivers of (dis)benefits. Highlights: (Dis)benefits of a marine use (mussel farming) are related to ecosystem services. It is shown that the ecosystem service concept relates to different planning phases. In each phase, different user-environment-beneficiary interactions can be addressed. The framework may increase social sustainability by considering (dis)beneficiaries.